Nonaqueous lithium storage element - Okada Nobuhiro; Kamijo Takeshi; Kaneko Akiko; Yamasaki Takashi; Mori Shiro (2017)
Provided is a nonaqueous lithium storage element which is obtained by housing an electrode body and a nonaqueous electrolyte solution containing a lithium salt in an outer case, said electrode body being composed of a negative electrode that is composed of a negative electrode collector and a negative electrode active material layer laminated on one or both surfaces of the negative electrode collector, a positive electrode that is composed of a positive electrode collector and a positive electrode active material layer laminated on one or both surfaces of the positive electrode collector, and a separator.